Hubungan Antara Hs-Crp Dengan Derajat Keparahan Lesi Angiografi Berdasarkan Gensini Scoring Pada Penderita Stable Angina di Surabaya - ANTOK WICAKSONO; INTAN KOMALASARI; SRI MULYATI (HANG TUAH MEDICAL JOURNAL, 2021)
Abstract Background: Coronary heart disease (CHD) is a disease that occurs due to coronary artery stenosis. This disease occurs due to accumulation of plaque in the coronary arteries, causing the artery lumen to stenosis. Stenosis of 70% or more will cause a disruption in myocardial oxygen supply and demand. The degree of stenosis can be assessed by the angiographic scoring system, namely the gensini score. Inflammation plays an important role in atherosclerosis. High Sensitivity C-Reactive Protein is a marker of inflammation that can play a risk factor as well as a predictor of coronary heart disease and can play a direct role in the atherosclerosis process. Objective: To determine the relationship between hs-CRP and the severity of angiographic lesions measured by gensini scoring in patients with stable angina at RSAL DR Ramelan Surabaya. Methods: Descriptive analytic study research. The research design uses cross sectional method and the sampling method used is purposive sampling. Samples were taken as many as 16 medical records and blood samples of CHD patients who underwent angiography and were measured using Gensini scores in Dr. Rumkital. Ramelan Surabaya. The research data is then processed descriptively. Results: A significance value of 0.001 <α (0.05) was obtained, and a correlation value of 0.726 showed an association between levels of hs-CRP and degree of angiography lesions based on gensini scores in patients with stable coronary heart disease in Dr. Rumkital Dr. Ramelan Surabaya. Conclusion: there is a significant relationship between increased levels of hs-CRP with the severity of angiographic lesions measured by gensini scores